MOLECULAR CHARACTERISATION OF METALLO-BETA LACTAMASE AND OTHER RESISTANCE GENES IN PSEUDOMONAS AERUGINOSA FROM SEVEN TERTIARY HOSPITALS IN SOUTHWESTERN NIGERIA (2019)
The emergence of resistance to carbapenems, a last resort antibiotic, among Pseudomonas aeruginosa is of great health concern. Detailed studies on the molecular basis of carbapenem resistance in clinical P. aeruginosa isolates are scanty in Nigeria. Therefore, this study was aimed at determining the incidence of Metallo-Beta Lactamase (MBL) and other mechanisms mediating carbapenem resistance, and evaluating clonal spread among carbapenem-resistant P. aeruginosa isolates. Four hundred and forty-seven presumptive P. aeruginosa isolates collected from seven tertiary hospitals laboratories in southwestern Nigeria were identified using biochemical tests and amplification of oprI and oprL genes. Antibiogram of the isolates and Minimum Inhibitory Concentrations (MIC) were determined by Kirby-Bauer disk diffusion and broth microdilution, respectively. Phenotypic detection of carbapenemases was carried out using Modified-Hodge and combined disc tests. Carbapenem-resistant P. aeruginosa isolates were screened for class A, B and D carbapenemases, integrons and type III secretion effectors by Polymerase Chain Reaction (PCR) followed by sequencing of amplified carbapenemase genes. Transferability of MBL genes was determined by transformation experiments. Quantitative reverse transcription PCR (RT-qPCR) was used to quantify expression levels of eight efflux pump genes, ampC cephalosporinase and outer membrane porin oprD. The isolates were further genotyped using three PCR-based fingerprinting techniques. Fisher’s exact test was used to determine the association between MBL and integrons at p ≤ 0.05. Four hundred and thirty isolates were identified as P. aeruginosa of which 185(43.0%) were multidrug resistant and 50(11.6%) were extensively drug resistant. All the isolates were resistant to ampicillin, cephalothin and cefuroxime, while sensitivity to polymyxin B was most common (96.3%). The MICs ranged from 0.125 to >64 µg/mL and 0.0625 to >64 µg/mL against imipenem and meropenem, respectively. All the isolates were negative for Modified-Hodge test, while combined disc test revealed the presence of MBL. Two class B carbapenemases were detected in 86.3% of the carbapenem resistant isolates: blaVIM and blaNDM in 35.6% and 38.4% isolates, respectively, co-existing in 12.3% isolates. Fifty-one (57.5%) carbapenem-resistant P. aeruginosa strains carried class 1 integrons while class 1 and 2 integrons were present concomitantly in 12.3%. Type III effector genes, exoY and exoT were found in all isolates, while exoU and exoS were present in 49.3% and 53.4%, respectively. Two isolates possessed both exoU and exoS. Sequence analysis of blaVIM and blaNDM revealed maximum identity with blaVIM-5 and blaNDM-1, respectively. MBL genes were successfully transferred into Escherichia coli DH5α. MexXY-OprM was the most overexpressed pump (5.0 - 996.3 fold increase) occurring in 58.3% of the isolates. The ampC was overexpressed in 27.1% isolates, while oprD porin down-regulation was observed in 77.1% of the isolates. Nine disseminated clones were identified across southwestern states. There was positive association between integrons and MBL (p = 0.0064). There is a high incidence of transmissible metallo-beta lactamase genes in Pseudomonas aeruginosa from tertiary hospitals in southwestern Nigeria with different mechanisms mediating carbapenem resistance. blaVIM-5 and blaNDM-1 were found co-occurring for the first time. There is a need for surveillance of resistance to carbapenems and associated resistance genes.